Transcriptomic Analysis of Gill and Hepatopancreas in Razor Clam (Sinonovacula constricta) Exposed to Acute Ammonia - Lv, Liyuan; Ren, Jianfeng; Zhang, Huan; Sun, Changsen; Dong, Yinghui; Lin, Zhihua (Frontiers in Marine Science, 2022)
Excessive ammonia accumulation is a big threat to aquatic animals that causes adverse effects on the health, production reduction, and even high mortality. The razor clam Sinonovacula contricta, a bivalve living in intertidal mudflat with a deep-burrowing lifestyle, often faces to high concentration of ambient ammonia. However, there is little available information concerning the toxic effects of ammonia on razor clam and its molecular mechanisms of adaptation to ammonia stress. The aim of this study is to investigate the effects of ammonia exposure on gill and hepatopancreas of razor clam by transcriptome sequencing. The results showed that the median lethal concentration of ammonia was 224.55 mg/L for 96 h. A total of 1,415 and 306 differentially expressed genes (DEGs) were identified in gill and hepatopancreas, respectively. The function annotation showed that DEGs of gill were mainly involved in regulation of nitrogen compound metabolic process, nitrogen compound transport and amide transport. The DEGs of hepatopancreas were mostly enriched in oxidation-reduction process, response to stress and amine metabolic process. The expression levels of NH3/NH4+ transporting and H+ excreting related genes, including Rhesus glycoproteins (Rh), Na+/K+(NH4+)-ATPase (NKA), Na+/H+ exchanges (NHE), V-ATPase (VHA), and carbonic anhydrase (CA), were up-regulated significantly in gill (P < 0.05). Additionally, the expression levels of glutamine and urea synthesis-related genes which played vital roles in ammonia detoxification, such as glutamine synthetase (GS), arginase (ARG) and argininosuccinate synthetase (ASS), were also increased obviously in hepatopancreas (P < 0.05). Taken together, our results indicate that the synergistic action of ammonia excretion in gill and ammonia metabolism in hepatopancreas might be the mechanism through which the clams tolerate to environmental ammonia. This study would provide a molecular basis for better evaluating the responding mechanism of ammonia tolerance.